Evidence of presynaptic and postsynaptic action of local anesthetics in rats - Braga,Angélica de Fátima de Assunção (2013)
PURPOSE: To assess the probable actions of ropivacaine, 50% enantiomeric excess bupivacaine mixture (S75-R25) and levobupivacaine on neuromuscular transmission in vitro. METHODS: Thirty rats were distributed into groups (n=5) according to the drug used: ropivacaine, bupivacaine (S75-R25) and levobupivacaine. The concentration used for the three local anesthetics (LA) was 5 µg.mL.-1The following parameters were evaluated: 1) LA effects on membrane potential (MP) and miniature end plate potential (MEPP). A chick biventer cervicis preparation was also used to evaluate LA effects on the contracture response to acetylcholine. RESULTS: LA did not alter MP values and decreased the frequency and amplitude of MEPP. In a chick biventer cervicis preparation, bupivacaine (S75-R25) and levobupivacaine decreased the contracture response to acetylcholine with statistical significance, in comparison to ropivacaine. CONCLUSIONS: In the concentrations used, levobupivacaine and bupivacaine (S75-R25) exhibited presynaptic and postsynaptic actions evidenced by alterations in miniature end plate potentials and contracture response to acetylcholine. Ropivacaine only had a presynaptic action.